2021
DOI: 10.1007/s10098-021-02180-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint in Higher Education Institutions: a literature review and prospects for future research

Abstract: Graphic abstract Higher Education Institutions (HEI) or universities, as organisations engaged in education, research and community services, play an important role in promoting sustainable development. Therefore, they are increasingly linked to the initiative of calculating their carbon footprint (CF), which is a tool to assess sustainability from the perspective of greenhouse gas (GHG) emissions. The aim of this study is to carry out a systematic review of the current situation of CF assessment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 68 publications
(79 reference statements)
1
60
1
Order By: Relevance
“…Likewise, in a particular way, the reduction in electrical energy consumption could be identified in the buildings and laboratories of some universities in Europe, with significant levels of decrease, as has been reported in some studies [25,35]. This translates into reduced environmental impact [36][37][38] and energy costs.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, in a particular way, the reduction in electrical energy consumption could be identified in the buildings and laboratories of some universities in Europe, with significant levels of decrease, as has been reported in some studies [25,35]. This translates into reduced environmental impact [36][37][38] and energy costs.…”
Section: Introductionmentioning
confidence: 85%
“…The mitigation of CO 2e emissions in universities, as in the rest of the world, as a result of the pandemic, is also significant [50] and it has been common in all the universities of the world [38]. In contrast, the reduction of CO 2 emissions as a result of the reduction of energy consumption in universities [38,46] has represented a mitigation strategy resulting from the pandemic, which has contributed to the reduction of the carbon footprint in the entire world's education sector [36].…”
Section: Methodsmentioning
confidence: 99%
“…Carbon footprint technology is still emerging as a means of benchmarking and comparison, especially regarding the precision of calculations and the consistency of measurement methods (Li, et al, 2021;Valls-Val and Bovea, 2021). Nevertheless, the implications of personal decisions must be discussed in further depth until a normative definition of responsible action towards emission reductions is developed (Kar, et al, 2015).…”
Section: Malaysian Highway Carbon Footprint Calculatormentioning
confidence: 99%
“…The assessment of the calculation of CF in HEIs has been considered as one of the initial steps towards campus environmental sustainability [ 15 , 16 ], and CF reporting the start of sustainable educational practices [ 17 ]. The CF of an organization can be defined as the measurement of total greenhouse gas (GHG) emissions caused directly and indirectly due to its activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no relevant references that evidence the use of CF as an environmental performance indicator in HEIs [ 14 ], the assessment of CF in these organizations is widely registered: The literature contains a few studies focused on comparing the CFs of different HEIs belonging to specific associations in a specific geographical area [ 16 ], such as Bailey and LaPoint [ 20 ], who compared the CF from nine universities located in Texas (USA) or Robinson et al [ 21 ] with 20 colleges in the United Kingdom. In some cases, they are very detailed studies, but pertaining to a single university, such as Abdelalim et al [ 22 ], which reported individual CFs for 42 buildings on the Carleton University campus in Canada.…”
Section: Introductionmentioning
confidence: 99%